2016
DOI: 10.7439/ijbar.v7i2.2945
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antimicrobial sensitivity pattern of Klebsiella pneumoniae from sputum samples in a tertiary care hospital

Abstract: Background: Gram negative pathogens are an important cause of community and hospital acquired infections throughout the world. Klebsiella pneumoniae has become one of the more common causes of these infections and one of the important aspects of Klebsiella associated infections is the emergence of multi-drug resistant strains particularly those involved in nosocomial diseases. This study was done to determine the isolation rate of Klebsiella, their antibiogram and for the presence of resistant strains from spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In the present study, 100% of the isolated K. pneumoniae from the sputum samples were resistant to ampicillin, and approximately 78% of the isolates were sensitive to gentamicin. This is in line with the results of a study conducted in India, which indicated that 92% of the Klebsiella isolates from sputum showed resistance to ampicillin (8). However, this is inconsistent with the other studies that indicated that the majority of the strains isolated from sputum were sensitive to amikacin (24).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, 100% of the isolated K. pneumoniae from the sputum samples were resistant to ampicillin, and approximately 78% of the isolates were sensitive to gentamicin. This is in line with the results of a study conducted in India, which indicated that 92% of the Klebsiella isolates from sputum showed resistance to ampicillin (8). However, this is inconsistent with the other studies that indicated that the majority of the strains isolated from sputum were sensitive to amikacin (24).…”
Section: Discussionsupporting
confidence: 59%
“…It is estimated that approximately 700,000 deaths occur each year due to AMR. Furthermore, it is predicted that if appropriate control and prevention measures are not taken, AMR could become a leading cause of mortality in hospitalized and non-hospitalized patients in developing and developed countries (8).…”
Section: Introductionmentioning
confidence: 99%